MANFAAT TEKNOLOGI KOMPUTER DALAM PENYELENGGARAAN BIMBINGANDAN KONSELING SECARA ONLINE DALAM BENTUK E_KONSELING - Fitri Latifah (Universitas Bina Sarana Informatika, 2012)
Guidance and koseling is one of the most important aspects in the education system. The instructoras one who has a supporting role and responsibilities as guidance and educational supportservices, are required to have sufficient insight to the concept - the basic concepts of guidance andcounseling. The use of current computer technology has provided opportunities for guidance andcounseling to develop concepts and ways to build e_konseling guidance counseling. With thee_konseling then the distance of space and time are not an obstacle to the counselee that will dothe consultation and guidance counselor. Media in e_konseling allow the counselee to makecontact with on_line ways such as using E_mail, chat, or other media transformation. Onlinecounseling is a counseling activity-based virtual relationships with clients based on the needs thathave a distance and still hesitant to be more open to others advantage of an online counselingservice is to provide services that are inexpensive, easy and guaranteed confidentiality and that isunbelievably broad coverage across the region who already have Internet access. In additionthere are advantages disadvantages of online services such as online mendia will make it difficultfor people who do not understand computer technology and Internet-based mobile phone andcatting, another drawback is the counselor can not understand and assess emotional counselingcounselees because the implementation is not in physical contactKey word : Guideance and counseling, e_counseling, online system